Preclinical Drug Metabolism and Pharmacokinetics, and Prediction of Human Pharmacokinetics and Efficacious Dose of the Investigational Aurora A Kinase Inhibitor Alisertib (MLN8237) - J. Yang, Johnny; Li, Yu; Chakravarty, Arijit; Lu, Chuang; Q. Xia, Cindy; Chen, Susan; Pusalkar, Sandeep; Zhang, Mengkun; Ecsedy, Jeffrey; G. Manfredi, Mark; Wu, Jing-Tao; Chyi Shyu, Wen; et al. (Drug Metabolism Letters, 2013)
Alisertib (MLN8237) is an investigational potent Aurora A kinase inhibitor currently under clinical trials for hematological and nonhematological malignancies. Nonclinical investigation showed that alisertib is a highly permeable compound with high plasma protein binding, low plasma clearance, and moderate volume of distribution in rats, dogs, monkeys and chimpanzees. Consistent with the above properties, the oral bioavailability in animals was greater than 82%. The predicted human oral pharmacokinetic (PK) profile was constructed using allometric scaling of plasma clearance and volume of distribution in the terminal phase from animals. The chimpanzee PK profiles were extremely useful to model absorption rate constant, which was assumed to be similar to that in humans, based on the fact that chimpanzees are phylogenetically closest to humans. The human plasma clearance was projected to be low of 0.12 L/hr/kg, with half-life of approximately 10 hr. For human efficacious dose estimation, the tumor growth inhibition as a measure of efficacy (E) was assessed in HCT116 xenograft mice at several oral QD or BID dose levels. Additionally, subcutaneous mini-pump infusion studies were conducted to assess mitotic index in tumor samples as a pharmacodynamic (PD) marker. PK/PD/E modeling showed that for optimal efficacy and PD in the xenograft mice maintaining a plasma concentration exceeding 1 μM for at least 8-12 hr would be required. These values in conjunction with the projected human PK profile estimated the optimal oral dose of approximately 103 mg QD or 62.4 mg BID in humans. Notably, the recommended Phase 2 dose being pursued in the clinic is close to the projected BID dose.
Keywords: MLN8237